Antibiotics for sore throat. - Mar, D; Glasziou, P; Spinks, AB (2004)
BACKGROUND: Sore throat is a very common reason for people to seek medical care. It is a disease that remits spontaneously, that is, 'cure' is not dependent on treatment. Nonetheless primary care doctors commonly prescribe antibiotics for sore throat and other upper respiratory tract infections. OBJECTIVES: To assess the benefits of antibiotics in the management of sore throat. SEARCH STRATEGY: Systematic search of the literature from 1945 to 2003, using electronic searches of the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, issue 2, 2003); MEDLINE (January 1966 to May 2003); EMBASE (January 1990 to March 2003), and the reference sections of the articles identified. We applied no language restrictions. We used abstracts of identified articles to identify trials. SELECTION CRITERIA: Trials of antibiotic against control with either measures of the typical symptoms (throat soreness, headache or fever), or suppurative complications (meaning: forming pus) and non-suppurative complications of sore throat. DATA COLLECTION AND ANALYSIS: Two reviewers independently screened potential studies for inclusion and resolved differences in opinion by discussion. The reviewers then independently extracted the data from the selected studies. We contacted the authors of three studies to acquire additional information not available in published articles. Potential studies were screened independently by two reviewers for inclusion, with differences in opinion resolved by discussion. Data was then independently extracted from studies selected by inclusion by two reviewers. Authors of three studies were contacted to acquire additional information not available in published articles. MAIN RESULTS: We included twenty-six studies, covering 12,669 cases of sore throat in the review.1. Non-suppurative complications There was a trend for protection against acute glomerulonephritis by antibiotics, but insufficient cases were recorded to be sure of this effect. Several studies found that antibiotics reduced acute rheumatic fever, to less than one third (odds ratio (OR) = 0.30; 95% confidence interval (CI) = 0.20 to 0.45). 2. Suppurative complications Antibiotics reduced the incidence of acute otitis media to about one quarter of that in the placebo group (OR = 0.22; 95% CI 0.11 to 0.43) and reduced the incidence of acute sinusitis to about one half of that in the placebo group (OR = 0.46; 95% CI 0.10 to 2.05). The incidence of quinsy was also reduced in relation to placebo group (OR = 0.16; 95% CI 0.07 to 0.35). 3. Symptoms Symptoms of headache, throat soreness and fever were reduced by antibiotics to about one half. The greatest time for this to be evident was at about three and a half days (when the symptoms of about 50% of untreated patients had settled). About 90% of treated and untreated patients were free of symptoms by one week. The overall number needed to treat to prevent one sore throat at day three was about 5.0 (95% CI 4.5 to 5.8); and at one week was 14.2 (95% CI 11.5 to 20.6). 4. Subgroup analyses of symptom reduction Subgroup analysis by age; blind versus unblinded; or use of antipyretics yielded no significant differences. The results of swabs of the throat for Streptococcus influenced the effect of antibiotics. If the swab was positive, antibiotics were more effective (the OR reduced to 0.16, 95% CI 0.09 to 0.26) than if it was negative (OR 0.65; 95% CI 0.38 to 1.12). REVIEWERS' CONCLUSIONS: Antibiotics confer relative benefits in the treatment of sore throat. However, the absolute benefits are modest. Protecting sore throat sufferers against suppurative and non-suppurative complications in modern Western society can be achieved only by treating with antibiotics many who will derive no benefit. In emerging economies where rates of for example acute rheumatic fever are high, the number needed to treat may be much lower. Antibiotics shorten the duration of symptoms by a mean of one day about half way through the illness (the time of maximal effect), and by about sixteen hours overall.